The Effect of Situational Leadership Behavior Organizational Culture and Human Resources Management Strategy on Education and Training Institution Productivity (Survey on Educational and Vocational Training Institutions in West Java Province) - Iskandar Iskandar (International Journal of Nusantara Islam, 2013)
The aim of this research is to analyze: situational leadership behavior, organizational culture and productivity of vocational training institutes in west Java Province. The correlation between situational leadership behavior and organizational culture at vocational training institutes, the effect of situational leadership behavior and organizational culture toward productivity of vocational training institutes in west Java Province. This research uses organizational behavior and human resources management approach. The type of the research is descriptive and verificative, while the method used both descriptive and explanatory survey. Investigation type is casualty and time horizon in cross sectional. The sample size used is proportionate sampling by taking sample 115 vocational training institute of spread over 19 locations totally, all its population counted 719 vocational training institutes in west Java Province. The data analyzed by descriptive analytic and path analysis. The result of research shows, 1) situational leadership behavior and organizational culture in generalities, rather high score and the productivity at vocational training institutes to society, cooperation with company or industry in training program development, and placement of training graduate assessed by rather low, 2) there is correlation which significant between situational leadership behavior and organizational at vocational training institutes in west Java Province, 3) situational leadership behavior, organizational culture has significant effect simultaneously and partially productivity of vocational training institutes in west Java Province.